Work motivation and organizational climate in telecommunication companies from an organizational behaviour view point (2006)
The present study arose from a research carried out in Bogotá's telecommunications sector, which was orientated towards describing and comparing motivational factors and their relationship to the organizational climate concerning employees from both a public and a private company. The results were analysed by comparing the means from different motivational factors and work climate dimensions regarding some demographic variables. These served as a point of comparison, contrast or affinity for describing and analysing both companies' work motivation and organisational climates. It was concluded that there were no significant differences regarding work climate and motivation of public and private company workers in the telecommunications sector, contrasting with the popular belief that there is relatively low commitment in state companies. There could be cultural and legal differences.